From Cold War politics to post-Cold War fiction: Philip Roth’s "I married a communist" and the problem of cultural pluralism - Löffler, Philipp (College literature, 2015)
I Married a Communist is arguably one of the most understudied Philip Roth novels. This article makes two claims that underline the book’s unacknowledged centrality both within the immediate context of the so-called “American Trilogy” and as a powerful example of post–Cold War historical fiction. First, despite its seemingly realist ambition, the novel denounces traditional truth questions in historical writing (and their skeptical rebuttal) and instead focuses on the uses of history as potential forms of world-making. Second, I Married a Communist complicates the notion that only the end of the Cold War conditioned the general turn away from ideology questions in favor of a dubious identitarian pluralism—a point variously reiterated and critiqued after Walter Michaels’s Shape of the Signifier (2004)—by arguing that such pluralistic desires in fact emerged in a necessary historical co-evolution with the rise of ideological antagonism during the 1940s and 1950s. Storytelling is featured in the novel as a pluralistic form of world-making to stress exactly this point.
Gesehen am 04.09.2019